Primerjava pravilnosti izračunov zdravil v zdravstveni negi med tradicionalnimi metodami in uporabo mobilne aplikacije - Gogova, Tina (Obzornik zdravstvene nege, 2026)
Introduction: Calculating medication doses and flow rates represents a critical component of nursing practice, directly impacting treatment safety and patient health. Expert estimates indicate that nursing calculations are accurate in 60–90% of cases. Digital technology holds significant potential to minimise medication calculation errors. The aim of this study was to determine whether the NurseCal mobile app enhances the accuracy and speed of medication dosage calculations among nursing students compared to traditional calculation methods.Methods: To evaluate the impact of the NurseCal mobile app, this study used a quantitative, quasi-experimental, non-equivalent control group post-test-only research design and was conducted among second and third-year nursing students (n = 198) in April 2022. The control group completed seven calculations manually, while the experimental group used the NurseCal app. Data were analysed using the Shapiro-Wilk test and the Mann-Whitney U test.Results: Students using the NurseCal mobile app completed the calculations more quickly (U = 619, p = 0.001) and with statistically significantly greater accuracy (U = 7372, p < 0.001).Discussion and conclusion: The study confirmed the usability of the NurseCal mobile app for calculating medication doses and flow rates among students, which could reduce errors. There is potential for the use of this mobile app in both educational and healthcare settings, but further research is needed to explore its use in clinical practice with other populations and larger samples.
Keywords: cancer safety incident; digital technology; digitalna tehnologija; education; family-centered care; health care; izobraževanje; matematične spretnosti; mathematical skills; varnostni odklon; zdravstvena nega